Pycnandra longiflora (Sapotaceae) a species believed to be extinct, rediscovered in New Caledonia - Munzinger, Jérôme; Swenson, Ulf (Phytotaxa, 2016)
Pycnandra longiflora (Sapotaceae) belongs to the largest endemic genus in New Caledonia. It is only known from the type collection made in 1861–67 at the obscure locality “Gatope”. Relocation of this species has been of high priority for more than a decade, but without success. Pycnandra longiflora was therefore recently declared extinct. However, a population was recently discovered near a mining site at Onajiele, in the Ouazangou-Taom massif, and it is revealed that P. longiflora has the most spectacular flowers in the entire genus, being large and bicoloured in red and yellow. A thorough description is here outlined and we propose a preliminary IUCN status as Critically Endangered.